Prostaglandin E2 Antagonizes TGF-β Actions During the Differentiation of Monocytes Into Dendritic Cells - Remes Lenicov, Federico; Paletta, Ana Luz; Gonzalez Prinz, Melina; Varese, Augusto; Pavillet, Clara E.; Lopez Malizia, Álvaro; Sabatté, Juan; Geffner, Jorge Raul; Ceballos, Ana (Frontiers in Immunology, 2018)
Inflammatory dendritic cells (DCs) are a distinct subset of DCs that derive from circulating monocytes infiltrating injured tissues. Monocytes can differentiate into DCs with different functional signatures, depending on the presence of environment stimuli. Among these stimuli, transforming growth factor- (TGF-) and prostaglandin E2 (PGE2) have been shown to modulate the differentiation of monocytes into DCs with different phenotypes and functional profiles. In fact, both mediators lead to contrasting outcomes regarding the production of inflammatory and anti-inflammatory cytokines. Previously, we have shown that human semen, which contains high concentrations of PGE2, promoted the differentiation of DCs into a tolerogenic profile through a mechanism dependent on signaling by E-prostanoid receptors 2 and 4. Notably, this effect was induced despite the huge concentration of TGF-β present in semen, suggesting that PGE2 overrides the influence exerted by TGF-β. No previous studies have analyzed the joint actions induced by PGE2 and TGF-β on the function of monocytes or DCs. Here, we analyzed the phenotype and functional profile of monocyte-derived DCs differentiated in the presence of TGF-β and PGE2. DC-differentiation guided by TGF-β alone enhanced the expression of CD1a and abrogated LPS-induced expression of IL-10, while differentiation in the presence of PGE2 impaired CD1a expression, preserved CD14 expression, abrogated IL-12 and IL-23 production, stimulated IL-10 production, and promoted the expansion of FoxP3+ regulatory T cells in a mixed lymphocyte reaction. Interestingly, DCs differentiated in the presence of TGF-β and PGE2 showed a phenotype and functional profile closely resembling those induced by PGE2 alone. Finally, we found that PGE2 inhibited TGF-β signaling through an action exerted by EP2 and EP4 receptors coupled to cyclic AMP increase and PKA activity. These results indicate that PGE2 suppresses the influence exerted by TGF-β during DC differentiation, imprinting a tolerogenic signature. High concentrations of TGF-β and PGE2 are usually found in infectious, autoimmune and neoplastic diseases. Our observations suggest that in these scenarios PGE2 might play a mandatory role in the acquisition of a regulatory profile by DCs.